(untitled) (Physical Education, Health and Social Sciences, 2025)
This study empirically examines how Leader Cultural Intelligence (LCI) affects problem-solving (PS) of employees and it also investigates psychological safety as mediator between LCI and employee PS. It also investigates cognitive diversity’s moderating role on this mediated pathway. Using survey data collected from 400 employees operating in telecommunication contact centers in Pakistan, the results confirm a positive relationship between LCI and employees’ problem-solving while psychological safety mediates this relationship. In addition, the study unveils cognitive diversity as a moderator that adjusts the relationship between psychological safety and problem-solving skills. These contributions enhance theoretical discussion as well as managerial practice, especially in multicultural organizational environments where different national teams need to work closely together.